Desenvolvimento e caracterização de sistema mucoadesivo termossensível contendo micropartículas de própolis para potencial tratamento de candidíase vulvovaginal - Ferreira, Sabrina Barbosa de Souza (2011)
Vulvovaginal candidiasis is a fungal infection of vulva and vagina, caused by several species of Candida, mainly by C. albicans. The conventional treatment is accomplished through the administration of imidazole and triazole compounds, and polyenic agents, leading to serious problems of intolerance and toxicity in the gastrointestinal tract. In the last years, several studies were made proving the antimicrobial activity of propolis, especially by promoting a potentially effective treatment, with safe and low cost. In addition, currently the goal is the localized action of the drug by the use of thermo-sensitive mucoadhesive systems. Thus, the study aimed to develop and characterize a thermo-sensitive mucoadhesive system containing microparticles of propolis for the treatment of vulvovaginal candidiasis. Then, propolis was collected in the Northwest region of Paraná State and their quality was evaluated. It was prepared and evaluated the quality of the drug extract, validated analytical methods for quantification; developed and characterized a thermo-sensitive mucoadhesive system, composed of poloxamer 407 and Carbopol 934P®, containing microparticles of propolis. It was held in vitro antifungal evaluation of propolis extract and from the system is well. The propolis and extractive solution showed good quality which proved to be suitable for use in the production of microparticles in situ of the drug. The analytical methodologies were validated, two systems were developed, with different proportions of the polymers, which showed the gelation temperature, mechanical and rheological properties, mucoadhesion and content of propolis appropriate to release into the vaginal cavity. The propolis extract and systems demonstrated in vitro antifungal activity against reference strains and clinical isolates. The determination of in vitro release profile of propolis from system showed that propolis can be released in a controlled way for a period of 24 hours.